Open call for disruptive agri-tech solutions to support Morocco’s Generation Green 2020-2030 Strategy - Menza, Gianpiero; Zaccari, Claudia (2022)
The CGIAR Accelerate for Impact Platform, World Bank and its Digital Development Partnership trust fund, and IMPACT Lab announced the open call for applications for the AgriTech4Morocco Innovation Challenge.